Social Determinants of Women’s Reproductive Health from a Public Health Perspective - Abimulyani, Yumi (Oshada, 2026)
Women's reproductive health is fundamentally shaped by complex interplays of social, economic, cultural, and structural factors that extend far beyond biological determinants. This comprehensive review synthesizes current evidence on social determinants affecting reproductive health outcomes across diverse populations. Drawing from systematic reviews, scoping reviews, and empirical studies published between 2021 and 2025, we examine how socioeconomic status, education, gender norms, cultural practices, healthcare access, and structural inequalities influence contraceptive use, antenatal care attendance, maternal mortality, pregnancy complications, and overall reproductive autonomy. The evidence demonstrates that poverty and low educational attainment consistently correlate with unintended pregnancies, inadequate prenatal care, and increased maternal-infant morbidity and mortality. Patriarchal gender norms significantly constrain women's reproductive decision-making autonomy, particularly regarding contraception, birth spacing, and childbirth location. Geographic and financial barriers to quality healthcare services, compounded by provider attitudes and lack of youth-friendly or disability-inclusive services, further exacerbate health inequities. Structural determinants including racial and ethnic discrimination, migrant status, residential segregation, gender-based violence, and weak social support networks profoundly impact reproductive health quality of life. This review underscores the imperative for public health interventions that transcend clinical approaches to address social justice and gender equity as fundamental prerequisites for improving women's reproductive health outcomes globally